Modal Perusahaan Terhadap Nilai Profitabilitas Variabel Intervening Property dan Real Estate Terdaftar di BEI - Febby Yola Natasya; Teguh Setiawan; Hafriz Rifki Hafas (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
The data of this study were taken from the Indonesia Stock Exchange with the aim of knowing the effect of capital structure and firm size on firm value with profitability as an intervening variable in property and real estate companies. This research uses causality research method with quantitative approach with secondary data documentation data collection techniques. The total population of this study were 40 companies and the number of samples was 30 companies. Determination of the sample in this study using purposive sampling technique. The results of this study indicate that the capital structure variable has a significant positive effect on firm value, firm size has a significant negative effect on firm value, capital structure has a significant negative effect on profitability, firm size has a significant negative effect on profitability, profitability has a significant negative effect on firm value and profitability is not able to mediate capital structure and firm size on firm value.